Pledging, Praising and Shaming: Experimental Labour Markets in Ghana - Elwyn Davies; Marcel Fafchamps (Institute of Labor Economics (IZA), 2017)
Firm surveys have shown that labour management in developing countries is often problematic. Earlier experimental research (Davies & Fafchamps, 2017) has shown that managers in Ghana are reluctant to use monetary incentives to motivate workers. This paper presents the results from a gift-exchange game experiment in Ghana in which the worker can make a promise to the employer before a contract is offered (ex ante communication) and in which the employer can send negative or positive feedback to the worker after the worker has chosen effort (ex post communication). The results indicate that feedback can help sustain cooperate behaviour (high effort provision), but only if the wage offered is high enough. Feedback reinforces reciprocity concerns on the behalf of the worker. In particular positive messages (praising) leads to higher effort provision, no significant relation between negative feedback and effort can be found. Promises are related to higher effort, but do not necessarily lead to higher wages.
Keywords: C71; D2; D86; E24; O16; 330; worker incentives; gift exchange; effort; worker criticism; communication